Sobre morteros ibero-latinos del Valle del Ebro (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Recent archaeological studies have revealed that the little stamps considered to be bilingual have actually different messages. Neverthless, though not identical, the Latin stamp FL. ATILI L. S. is a parallel and profitable text for the interpretation  of  bilakeaiunatinenabiner. However, on the other hand, the Latin stamp PROTEMVS FECI[T] does not lose its similarity with the Iberian on (ba)boŕotenbotenin.
Keywords: Iberian; Ware Stamps; Ebro Valley; Bilingual Inscriptions; Epigraphy